Occipital Neuralgia: a noninvasive therapeutic approach - Pablo Jesús López-Soto; José Miguel Bretones-García; Verónica Arroyo-García; Margarita García-Ruiz; Eduardo Sánchez-Ossorio; María Aurora Rodríguez-Borrego (Universidade de São Paulo, 2018)
ABSTRACT Objective: to evaluate the application of a noninvasive intervention consisting of a postural modification using personalized models and osteopathy in people with occipital neuralgia. Method: retrospective study of the intervention performed in adult population with occipital neuralgia, consisting of postural modification using personalized plantar orthoses and osteopathy, in a study period of four years. The observed variables were: persistence of headache, alignment of the axes, plantar support, center of gravity and center of mass; medical interview data, visual analogue scale, Win-Track gait analysis system and Kinovea software for video analysis (clinical assessment instruments used). Results: a total of 34 records of people with occipital neuralgia were studied. A fraction of 58.8% of the patients reported improvement after the intervention. The visual analogue scale data were provided for 64.7% of the records and significant differences (p <0.001) between the means before (8.4 ± 1.7) and after the intervention (2.6 ± 2.7) were found. Conclusion: postural modification using personalized orthoses and osteopathy substantially improves the symptomatology of patients with occipital neuralgia.